Decision-making processes as predictors of relapse and subsequent use in stimulant-dependent patients. (2nd January 2016) - Adinoff, Bryon; Carmody, Thomas J.; Walker, Robrina; Donovan, Dennis M.; Brigham, Gregory S.; Winhusen, Theresa M.
ABSTRACT: Background : Decision-making processes have been posited to affect treatment outcome in addicted patients. Objective : The present multi-site study assessed whether two measures of decision-making predicted relapse and subsequent use in stimulant-dependent patients. Methods : A total of 160 methamphetamine- or cocaine-dependent patients participating in a multi-site clinical trial evaluating a modified 12-step facilitation intervention for stimulant-dependent patients (STAGE-12) were assessed. Decision-making processes of risk and delay (Iowa Gambling Task [IGT]) and response reversal (Wisconsin Card Sorting Task [WCST]) were obtained shortly after treatment admission followed by assessment of stimulant use over the next six months. The relationships of the IGT and WCST (Perseverative Errors) with relapse (yes/no) and days of stimulant use during the 6-month period following post-randomization were evaluated. Results : Performance on the IGT and WCST did not significantly predict relapse status or time to relapse. Unexpectedly, worse performance on the IGT was associated with a fewer number of stimulant use days ( p = 0.001). In contrast, worse performance on the WCST (more perseverative errors) was associated with a greater number of stimulant use days ( p = 0.0003). The predictive effects of perseverative errors on subsequent use were confined to methamphetamine-dependent and Minority participants. Conclusions : Decision-making processes, as measured in the current study, do not uniformly predict relapse or subsequent use. A decrease in the salience attribution of non-drug reinforcers may explain the positive relationship between IGT performance and post-relapse use. More comprehensive and global measures of impulsiveness may better assess relapse risk and use.